Affectivity, conflicts in the work-family interface, and hotel employee outcomes - Karatepe, Osman M.; Uludag, Orhan (Elsevier Sci Ltd, 2008)
Based on data obtained from frontline hotel employees in Turkey, the current study examined the effects of negative affectivity (NA) and positive affectivity (PA) on work-family conflict and family-work conflict and the effects of both directions of conflict on marital satisfaction and turnover intentions. This study also tested the relationship of marital satisfaction with frontline employees' turnover intentions. The results demonstrated that PA ameliorates both work-family conflict and family-work conflict, while NA exacerbates only work-family conflict. The findings of the study indicated that family-work conflict has a detrimental impact on marital satisfaction. However, this study provided no empirical support for the relationship between work-family conflict and marital satisfaction. Consistent with the study predictions, frontline employees' perceptions of work-family conflict and family-work conflict increased their turnover intentions. There was also empirical support for the hypothesis that marital satisfaction has a significant negative impact on frontline employees' turnover intentions. Implications of the empirical results and limitations of the study are discussed. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: negative affectivity; positive affectivity; work-family conflict; family-work conflict; marital satisfaction; turnover intentions; turkey